Associations between empathy and big five personality traits among Chinese undergraduate medical students. - Yang Song; Meng Shi (PLoS ONE)
Background Empathy promotes positive physician-patient communication and is associated with improved patient satisfaction, treatment adherence and clinical outcomes. It has been suggested that personality traits should be taken into consideration in programs designed to enhance empathy in medical education due to the association found between personality and empathy among medical students. However, the associations between empathy and big five personality traits in medical education are still underrepresented in the existing literature and relevant studies have not been conducted among medical students in China, where tensions in the physician-patient relationship have been reported as outstanding problems in the context of China's current medical reform. Thus, the main objective of this study was to examine the associations between empathy and big five personality traits among Chinese medical students. Methods A cross-sectional study was conducted in a medical university in Northeast China in June 2016. Self-reported questionnaires including the Interpersonal Reactivity Index (IRI) and Big Five Inventory (BFI) and demographic characteristics were distributed. A total of 530 clinical medical students became our final subjects. Hierarchical regression analysis was performed to explore the effects of big five personality traits on empathy. Results Results of this study showed that big five personality traits accounted for 19.4%, 18.1%, 30.2% of the variance in three dimensions of empathy, namely, perspective taking, empathic concern and personal distress, respectively. Specifically, agreeableness had a strong positive association with empathic concern (β = 0.477, P<0.01), and a moderate association with perspective taking (β = 0.349, P<0.01). Neuroticism was strongly associated with personal distress (β = 0.526, P<0.01) and modestly associated with perspective taking (β = 0.149, P<0.01). Openness to experience had modest associations with perspective taking (β = 0.150, P<0.01) and personal distress (β = -0.160, P<0.01). Conscientiousness had a modest association with perspective taking (β = 0.173, P<0.01). Conclusion This study revealed that big five personality traits were important predictors of self-reported measures of both cognitive and affective empathy among Chinese medical students. Therefore, individualized intervention strategies based on personality traits could be integrated into programs to enhance empathy in medical education.